Complex Queries in a Shared Multi User Relational Cloud Database - Sidorov, Vasily (2017)
While DaaS is becoming more and more popular enterprises start considering it as an option to reduce IT maintenance costs. But data privacy and security issues keep most of them from moving to the cloud. Existing schemes of encrypting the database usually either provide a very basic search only and nothing more or give users more flexibility at a cost of data security. In this paper we try to introduce a highly secure and flexible database encryption scheme allowing multiple users to perform more complex queries, including cross-table joins and still achieve acceptable performance by utilizing database's built-in indexing capabilities. Several dedicated proxy servers in between the user and the database server help to achieve this and make it all transparent for the user. Developed solution shows acceptable performance level in most of the testing cases.